Investigating the prevalence of Bark beetles of Pinus halepensis in the North East semi-arid region of Algeria - Lyès Moumeni (MBI & UNS Solo, 2021)
Abstract. Moumeni L, Gastebois A, Gillmann L, Papon N, Benia F, Bouchara J-P, Bounechada M. 2021. Investigating the prevalence of Bark beetles of Pinus halepensis in the North East semi-arid region of Algeria. Biodiversitas 22: 2755-2762. Aleppo pine is the most common tree in the semi-arid forests of Algeria. Despite its high resistance to drought and adaptability to all types of soils, the effects of climate change are affecting it directly and indirectly. Stressed trees indeed are subject to bark beetle attacks. In this study, we sampled the bark beetles directly from the affected pine trees. Six species belonging to the Scolytinae subfamily were identified. Tomicus detruens and Orthotomicus erosus were widely spread and present in the three studied forests, where they were found to colonize living trees while Crypturgus numidicus, Crypturgus mediterraneus, Hylurgus ligniperda and Hylurgus micklitzi colonized only dead trees. Together with future identification of the microfungi associated with these xylophagous insects, these data may help to define prevention measures to fight the decline of Aleppo pine forests observed in some parts of Eastern Algeria.